The lower limit of normal versus a fixed ratio to assess airflow limitation: will the debate ever end?. Issue 3 (29th March 2018) - Smith, Lewis J.
A normal test result is typically differentiated from an abnormal result by identifying those values that fall within (normal) and outside (abnormal) the 95% confidence interval for that test, after the test is evaluated in healthy individuals from the intended population. This approach acknowledges that 5% of a normal population will have an abnormal test result and some individuals with a normal test result will have the disease the test is designed to identify. Such trade-offs are common in the practice of medicine. Identifying airflow limitation using an FEV1 /FVC less than 0.70 in a general population of young adults can no longer be justified http://ow.ly/MRzo30iWja5